An empirical Study about Fifty-Two Years of Organized Tourism in Sri Lanka (1966-2018) - Yohani, A.K.D.T (Staff Development Unit, Faculty of Social Sciences, University of Kelaniya, Sri Lanka., 2020)
Tourism industry will continue to be a key growth area for Sri Lanka. The economic potential of the industry is significant nowadays. Undoubtedly, it needs clear focus and attainable goals for the development. This research study aims to provide a backdrop for the development of tourism in Sri Lanka in relation to the Worldwide Hospitality and Tourism Themes (WHTT) issues on tourism in Sri Lanka. The research study is an opportunity to reflect on the best path forward for the industry. Moreover, this research study is written in the context of a strategic question, “how might post-war in Sri Lanka develop inbound tourism?” A narrative approach is taken to cover a period of 52 years. The data collection of the study was completed according to the annual reports, interviews and the Tourism Management Information System (Database of arrival/departure statistics, annual economic indicators etc.) Research findings indicate how 46 years of war affected tourism in Sri Lanka resulting in low demand, low prices and a reputation as a cheap destination in the industry. Sri Lanka passed two milestones in its tourism history by emerging as a “million tourist destination” and a “billion dollar export income earner” in 2012. Tourism has the potential to emerge as a major export income earner in Sri Lanka. Sri Lanka aims to attract four million tourists by 2020 as a future goal. To further develop the tourism industry, Sri Lanka must develop long-term plans, tourism master plans with inputs from all stakeholders. Tourism vision 2025 aims to position Sri Lanka strategically on the international tourism market, and to promote growth in tourism and the overall economy. Its goals include making tourism as the country’s second biggest generator of foreign exchange income and boosting sector employment to 1 million people. In conclusion, it can be stated that the past developments in the industry can be used to understand the path for future.
Keywords: Development, Planning, Market trends, arrivals, organized tourism